2012
DOI: 10.1086/663197
|View full text |Cite
|
Sign up to set email alerts
|

Poison Frog Colors Are Honest Signals of Toxicity, Particularly for Bird Predators

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. abstract: Antipredator defenses and warning signals typically evolve in concert. However, the extensive variation across taxa in both these components of predator deterrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
230
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(241 citation statements)
references
References 77 publications
7
230
1
3
Order By: Relevance
“…Some of the species found to have geographically varying warning signals include Neotropical Heliconius butterflies (Brown & Benson 1974, Brower 1996, Mallet 2010, ladybird beetles (Creed 1966, Brakefield 1985, Dolenská et al 2009, Blount et al 2012, monarch butterflies (Brower 1958, Davis et al 2005, Davis et al 2012, newts (Mochida 2009, Mochida 2011, poison frogs (Daly & Myers 1967, Savage 1968, Summers et al 2003, Wang & Summers 2010, Wang 2011, Rudh et al 2011, Maan & Cummings 2012, Willink et al 2013, RichardsZawacki et al 2013, Hegna et al 2013b), velvet ants (Wilson et al 2012), alpine leaf beetles (Borer et al 2010), and bumble bees (Plowright & Owen 1980). Interestingly, some aposematic species appear to switch between aposematic and cryptic strategies across their distributions.…”
Section: Geographic Variation For Different Preymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the species found to have geographically varying warning signals include Neotropical Heliconius butterflies (Brown & Benson 1974, Brower 1996, Mallet 2010, ladybird beetles (Creed 1966, Brakefield 1985, Dolenská et al 2009, Blount et al 2012, monarch butterflies (Brower 1958, Davis et al 2005, Davis et al 2012, newts (Mochida 2009, Mochida 2011, poison frogs (Daly & Myers 1967, Savage 1968, Summers et al 2003, Wang & Summers 2010, Wang 2011, Rudh et al 2011, Maan & Cummings 2012, Willink et al 2013, RichardsZawacki et al 2013, Hegna et al 2013b), velvet ants (Wilson et al 2012), alpine leaf beetles (Borer et al 2010), and bumble bees (Plowright & Owen 1980). Interestingly, some aposematic species appear to switch between aposematic and cryptic strategies across their distributions.…”
Section: Geographic Variation For Different Preymentioning
confidence: 99%
“…Although it is well established that females prefer color morphs that are similar to their own coloration (Summers et al 1999, Maan & Cummings 2008, recent work has shown that predators may not select for local morphs on the basis of color alone (Hegna et al 2013b, Richards-Zawacki et al 2013. Instead, base coloration of O. pumilio may be related to their toxicity (Maan & Cummings 2012). Therefore, a possible synergistic effect between sexual and warning signaling, and how an element of honest signaling of toxicity may further interact certainly poses many questions for future work (Cummings & Crothers 2013).…”
Section: Trait Trade-offs and Interactionsmentioning
confidence: 99%
“…Brown et al (2010) found evidence that divergence in dorsal color within the Bocas del Toro Archipelago was occurring more quickly than would be predicted under a neutral process, such as genetic drift. Underlying factors that might explain the warning signal diversity in the archipelago include sexual selection (Summers et al 1997;Maan and Cummings 2008;Tazzyman and Iwasa 2010;Rudh et al 2011) and predation (Siddiqi et al 2004;Reynolds and Fitzpatrick 2007;Saporito et al 2007b;Maan and Cummings 2008;Brown et al 2010;Wang and Summers 2010;Rudh et al 2011;Maan and Cummings 2012). Previous work has shown that the red morph of O. pumilio in Costa Rica is avoided by predators (Saporito et al 2007b), and that the black spotting pattern on the same morph does not influence the attack rate (Hegna et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In general, color elements that outline the body of an organism increase conspicuousness (Cuthill et al 2005). Maan and Cummings (2012) recently found that conspicuousness correlated with toxicity in O. pumilio, strengthening the hypothesis that coloration serves as an honest signal of unpalatability (but also see Daly and Myers 1967). A combination of the conspicuousness to avian predators and overall predicted higher visibility in complex environments suggests the red mainland morph of O. pumilio (and other similar morphs) may possess a more effective warning signal than other frogs in the complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation